Cross-language qualitative research studies dilemmas: a research review. (26th June 2020) - Mohamad Nasri, Nurfaradilla; Nasri, Nurfarahin; Abd Talib, Mohamad Asyraf
Abstract : Purpose: Cross-language qualitative research has gained momentum worldwide; yet, there is still a lack of consensus to guide researchers in ensuring the trustworthiness of the research. Several methodological dilemmas related to language differences between researchers and participants should be carefully addressed. Therefore, this study aims to (1) review qualitative literature addressing cross-language, (2) produce a list of methodological criteria and recommendations from the reviewed literature and (3) evaluate systematically published cross-language qualitative researches using the list. Design/methodology/approach: This study employed a summative content analysis of 35 published curriculum and pedagogy researches from 2000–2018 that viewed language differences as methodological issue. A list of 20 criteria or recommendations was constructed and used to evaluate the selected researches. Findings: The findings revealed that majority of the researches lacked understanding of language differences between researchers and participants causing multiple inconsistencies in reporting methodological issues. Failure to address these methodological issues could risk the trustworthiness of the data and the overall rigor of the research. Originality/value: This study highlights the importance to minimize methodological issues related to language differences. It is hoped that the list of criteria or recommendations proposed by this study could support other cross-language qualitative researchers in overcoming these methodological dilemmas.